2020
DOI: 10.3390/su122310139
|View full text |Cite
|
Sign up to set email alerts
|

How Eco is Eco-Tourism? A Systematic Assessment of Resorts on the Red Sea, Egypt

Abstract: Eco-tourism is a growing part of the tourism industry. However, there are no agreed-upon criteria of what constitutes eco-tourism, so the industry is currently self-identified, with eco-lodges simply declaring themselves so. Here we present the first systematic comparison of eco-tourism versus conventional (or mass) tourism, using as our study area a set of 37 resorts along the southern Red Sea coast of Egypt, all constructed on similarly oriented parcels between the sea and the Red Sea Mountain Range. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…As another practice, the green accommodation guests are increasingly encouraged to engage in PEBs relating to green practices such as reducing their electricity and water consumption, which is informed through information stickers in bedrooms and bathrooms [4,15,16]. For example, ecotourists who stay at an eco-lodge or green accommodation tend to be more involved in environmental matters than other types of nature-based tourists [21,22]. Targeting the guests staying in green hotels, a recent study by Han et al [1] provides empirical evidence indicating that green accommodation practices help the hotel guests to be aware of the benefits of the EMP and support the EMP at the hotel.…”
Section: Literature Review 21 Environmental Management Practices In the Green Accommodation Sectormentioning
confidence: 99%
“…As another practice, the green accommodation guests are increasingly encouraged to engage in PEBs relating to green practices such as reducing their electricity and water consumption, which is informed through information stickers in bedrooms and bathrooms [4,15,16]. For example, ecotourists who stay at an eco-lodge or green accommodation tend to be more involved in environmental matters than other types of nature-based tourists [21,22]. Targeting the guests staying in green hotels, a recent study by Han et al [1] provides empirical evidence indicating that green accommodation practices help the hotel guests to be aware of the benefits of the EMP and support the EMP at the hotel.…”
Section: Literature Review 21 Environmental Management Practices In the Green Accommodation Sectormentioning
confidence: 99%
“…Geographically speaking, Marsa Alam is the least established territory of the Red Sea governorate. With 8,553 inhabitants (as of the 2018 census), it is located on the outskirts of the governorate, almost 274 km from Hurghada, the well-developed and urbane regional center (Gohar & Kondolf, 2020). Marsa Alam's location on the Red Sea's western coastline in south-eastern Egypt makes it closer to the historical rural areas of Upper Egypt than Cairo, Egypt's capital.…”
Section: Research Trustworthinessmentioning
confidence: 99%
“…Marsa Alam's location on the Red Sea's western coastline in south-eastern Egypt makes it closer to the historical rural areas of Upper Egypt than Cairo, Egypt's capital. Its reputation as a tourist destination was augmented following the opening of Marsa Alam's International Airport in 2003 (Gohar & Kondolf, 2020).…”
Section: Research Trustworthinessmentioning
confidence: 99%
“…They evaluated the resorts based on environmental criteria that included swimming pool surface area, distance from mangrove areas, the proximity of flood plains, the amount of grass space, and methods of access to deep water. They concluded that self-identified ecotourism facilities were not considerably different from the regular ones (Gohar & Kondolf, 2020). Bratucu et al (2017) conducted a study on sustainable tourist development strategies in Romania's Carpathian Mountains, in which they confirmed that despite the fact that overdevelopment of mountain tourism may lead to environmental degradation and biodiversity loss, mountains and their landscapes are important resources for the tourism sector (Bratucu, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that the newer scope attracts attention towards the arising hazards concerning bio-system, stability of urban and resort buildings, as well as pollution of petrochemical factories (Abdallah, 2007). Gohar and Kondolf (2020) conducted a systematic comparison between ecotourism and conventional tourism, based on a group of 37 resorts along Egypt's southern Red Sea coast. All resorts were built on similarly oriented plots between the sea and the Red Sea Mountain Range.…”
Section: Introductionmentioning
confidence: 99%